WAWASAN AYAT-AYAT AL-QUR’AN DAN HADIS TENTANG PRODUKSI - Riyani Fitri Lubis (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
Production is a series of activities to produce goods not only for individuals but the community and other creatures aimed at the benefit. A series of activities are conducted in accordance with the guidance of Allah and the Messenger and the freedom to manage the various elements in production are given authority to man, but ownership is held by God. If done in accordance with the guidance it will be reward obtained. Humans have been given resources and knowledge, capital or property so that it can perform production by organizing into the organization so that better in producing. Allah also has clearly affirmed that humans are given privileges. Therefore work hard by using Reason and in accordance with the provisions of Allah and the Messenger because everyone has a responsibility to fellow Muslims in particular.